2003
DOI: 10.1128/iai.71.6.3563-3571.2003
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-12 p40 Secretion by Cutaneous CD11c+and F4/80+Cells Is a Major Feature of the Innate Immune Response in Mice That Develop Th1-Mediated Protective Immunity toSchistosomamansoni

Abstract: Radiation-attenuated (RA) schistosome larvae are potent stimulators of innate immune responses at the skin site of exposure (pinna) that are likely to be important factors in the development of Th1-mediated protective immunity. In addition to causing an influx of neutrophils, macrophages, and dendritic cells (DCs) into the dermis, RA larvae induced a cascade of chemokine and cytokine secretion following in vitro culture of pinna biopsy samples. While macrophage inflammatory protein 1␣ and interleukin-1␤ (IL-1␤… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
100
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(107 citation statements)
references
References 47 publications
6
100
1
Order By: Relevance
“…Neutrophils are an important source of chemokines which attract monocytes, MΦ and DC to the site of infection [52]. Indeed CCL3 and CCL4 are present at increased levels immediately after cercarial penetration [7]. The decline in CFDA-SE + neutrophils after 24 hrs is likely to reflect rapid degradation of labelled ES material due to their potent proteolytic activity [53] followed by their rapid clearance from the skin; none were observed in the sdLN.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils are an important source of chemokines which attract monocytes, MΦ and DC to the site of infection [52]. Indeed CCL3 and CCL4 are present at increased levels immediately after cercarial penetration [7]. The decline in CFDA-SE + neutrophils after 24 hrs is likely to reflect rapid degradation of labelled ES material due to their potent proteolytic activity [53] followed by their rapid clearance from the skin; none were observed in the sdLN.…”
Section: Discussionmentioning
confidence: 99%
“…CD14, another commonly used marker for monocytes and macrophages, binds bacterial LPS and is expressed on cells of monocytic lineage and is downregulated on cells that develop into mature myeloid dendritic cells (34,52). CD11c is often considered a hallmark of dendritic cells (8), however, several reports have shown that some macro-phage subsets can also express CD11c (20,31). Using this panel of markers, we have identified for the first time increases in CD11c-positive macrophages in adipose tissue, in response to a high-fat diet.…”
mentioning
confidence: 99%
“…This finding suggests that local factors in OVA-sensitized skin promote the expression of IFN-g. A potential candidate is increased numbers of myeloid DCs, which are a potent source of IL-12. 32 The impaired T H 1 response of mice inoculated with VV at sites of allergic skin inflammation was associated with the appearance of satellite pox lesions (Fig 1, B and C). However, these mice exhibited neither weight loss nor increased viral loads in skin or internal organs examined.…”
Section: Discussionmentioning
confidence: 91%